The Design of UDOO Boards: Contributing to the Appropriation of Digital Technology - Rizzo, Antonio; Caporali, Maurizio; Conti, Daniele; Montefoschi, Francesco; Burresi, Giovanni; Sinopoli, Bruno (Frontiers in ICT, 2019)
The domain of Human-Computer Interaction does not concern just the design of technology that is easy to use, useful, and fancy – it has to do with our role in shaping our environment, our ecological niche that today involves the whole earth. A key concept in the interaction between humans and computing resources is that of appropriation originally proposed by Aleksei Nikolaevich Leontiev. In the present paper we will first review the concept of appropriation and will present bricolage as a key activity for fostering appropriation. Then we will present the Makers Movement as a socio-cultural movement relevant for the process of appropriation of digital technology. Finally, we will describe our approach and vision in the design of the UDOO, a single board computer, and of a specific developing environment, UAPPI, for enabling the appropriation through meaningful activities of digital technologies.